A national survey of prisoners on antiretroviral therapy in Malawi: access to treatment and outcomes on therapy - Simon D. Makombe,1 Andreas Jahn,2,3 Hannock Tweya,2 Lameck Thambo,2 Joseph Kwong-Leung Yu,4 Bethany Hedt,5 Ralf Weigel,2 Amon Nkhata,1 Erik J. Schouten,1,6 Kelita Kamoto,1 Anthony D. Harries,1,7,8 (The Journal of Infection in Developing Countries, 2007)
Background: Malawi is making good progress scaling up antiretroviral therapy (ART), but we do not know the levels of access of high-risk, disadvantaged groups such as prisoners. The aim of this study was to measure access and treatment outcomes of prisoners on ART at the national level.Methodology: A retrospective cohort study was conducted examining patient follow-up records from all 103 public sector ART clinics in Malawi, and observations were censored on December 31, 2006.Results: By December 31, 2006, a total of 81,821 patients had been started on ART. Of these, 103 (0.13%) were prisoners. At ART initiation, 93% of prisoners were in World Health Organization (WHO) clinical stage 3 or 4 while 7% started in stage 1 or 2 with a CD4-lymphocyte count of .250/mm3. Treatment outcomes by the end of December 2006 were as follows: 66 (64%) alive and on ART at their registration facility; 9 (9%) dead; 8 (8%) lost to follow-up; and 20 (19%) transferred out to another facility. The probability of being alive and on ART at 6 and 12 months was 82.5% and 77.7%.Conclusions: In spite of the rapid scale-up of ART, only a small number of HIV-positive prisoners had accessed ART by the end of 2006. Treatment outcomes were good. Initiatives are now needed to improve access to HIV testing and ART in Malawifs prisons.